Analisis Kinerja Guru Bersertifikasi Di SMA Negeri 2 Maumere - Ernaningsih, Dian; Inâ€™am, Akhsanul (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to find out: 1) how the certified teacher's perception of the objectives of the certification program; 2) what are the obstacles faced by certified post-certified teachers in SMA Negeri 2 Maumere; 3) how the performance of certified teachers in Maumere 2 Public High Schools is reviewed in terms of pedagogical competence, personal competence, social competence, and professional competence. The research used a quantitative descriptive approach. The data was obtained using observation, interview, documents and question form against 27 certified teachers in SMA Negeri 2 Maumere. The results showed that: 1) the certified teacher perceptions against objective certification program indicate that teachers perceive certification program and its goal has helped the certified teachers, in particular, an increase in well-being. The teacher argued that certification program designed by the Government in addition to the increase in prosperity as well as for the achievement of increased professionalism, this is demonstrated by the efforts of certified teachers in SMA Negeri 2 Maumere in improving professionalism; 2. The resistance experienced by a teacher after teaching load i.e. certified demands quarterly filings with securities, the delay in the disbursement of allowances and the mastery of science and technology; 3. certified teacher Performance Sman 2 Maumere is at a good category for performance indicators on the competency of the pedagogic competence, personality, social competence and the competence of professionals.Keywords: Performance, Teacher, CertifiedÂ Abstrak: Penelitian ini bertujuan untuk mengetahui: 1) bagaimana persepsi guru bersertifikasi terhadap tujuan program sertifikasi; 2) apa saja hambatan yang dihadapi guru bersertifikasi pasca sertifikasi di SMA Negeri 2 Maumere; 3) bagaimana kinerja guru bersertifikasi di SMA Negeri 2 Maumere ditinjau dari kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial, dan kompetensi profesional. Penelitian menggunakan pendekatan kuantitatif deskriptif. Data yang diperoleh dari hasil observasi, wawancara, dokumen dan angket terhadap 27 guru bersertifikasi di SMA Negeri 2 Maumere. Hasil penelitian menunjukkan bahwa: 1) Persepsi guru bersertifikasi terhadap tujuan program sertifikasi menunjukkan bahwa guru memandang program sertifikasi beserta tujuannya telah membantu para guru khususnya guru bersertifikasi dalam peningkatan kesejahteraan. Guru berpendapat bahwa program sertifikasi dirancang oleh pemerintah selain peningkatan kesejahteraan juga untuk tercapainya peningkatan profesionalisme, hal ini ditunjukkan dengan upaya guru bersertifikasi di SMA Negeri 2 Maumere di dalam meningkatkan profesionalismenya; 2) Hambatan yang dialami oleh guru setelah tersertifikasi yaitu beban mengajar, tuntutan pemberkasan per triwulan, keterlambatan pencairan tunjangan dan penguasaan IPTEK; 3) Kinerja guru bersertifikasi SMA Negeri 2 Maumere berada pada kategori baik untuk indikator kinerja pada kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial dan kompetensi profesional.Kata kunci: Kinerja, Guru, Sertifikasi